2016
DOI: 10.1371/journal.pntd.0004364
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Screening Assay Identifies Monotherapy with Interferon-ß and Combination Therapies with Nucleoside Analogs as Effective Inhibitors of Ebola Virus

Abstract: To date there are no approved antiviral drugs for the treatment of Ebola virus disease (EVD). While a number of candidate drugs have shown limited efficacy in vitro and/or in non-human primate studies, differences in experimental methodologies make it difficult to compare their therapeutic effectiveness. Using an in vitro model of Ebola Zaire replication with transcription-competent virus like particles (trVLPs), requiring only level 2 biosafety containment, we compared the activities of the type I interferons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 32 publications
4
39
1
Order By: Relevance
“…A recent publication reported that HIV-1 drugs inhibit EBOV virus-like particles (trVLPs) that undergo a single cycle of transcription and replication [16]. The drugs showed activity alone or in combination against the transcription-competent trVLPs, but limited efficacy against EBOV-eGFP [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication reported that HIV-1 drugs inhibit EBOV virus-like particles (trVLPs) that undergo a single cycle of transcription and replication [16]. The drugs showed activity alone or in combination against the transcription-competent trVLPs, but limited efficacy against EBOV-eGFP [16].…”
Section: Resultsmentioning
confidence: 99%
“…The drugs showed activity alone or in combination against the transcription-competent trVLPs, but limited efficacy against EBOV-eGFP [16]. To investigate further these findings, we repeated the studies using the same cell lines, compound source, time of drug addition, and length of infection time to compare with the conditions we used to perform the drug screen study on EBOV/Mak (S2 Fig).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this screen, the drug Tasigna was not retested due to compound unavailability, but additionally, the drug Gleevec was included since it was reported to operate via the same mechanism and demonstrated better in vitro efficacy. The in vitro screens used viral RNA levels as a readout based on previous antiviral testing work [33] and infectious doses of MOI 0.01–0.1, similar to levels used in other anti-EBOV testing studies [6,34,35]. Given that the compounds tested in our study were chosen due to their perceived potential effectiveness for use against EBOV, the negative results demonstrate the importance of testing therapies using the actual live pathogen to determine effects.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, six doses of human IFN-β (10.5 ug/kg) administered subcutaneously (SC) extended the survival time of NHPs challenged with EBOV or Marburg virus , but did not improve the survival rate [53], suggesting that IFN treatments might be beneficial, but likely not fully protective by themselves. Based on the in vitro observation that IFN-β could inhibit the replication of recombinant EBOV in HEK293 cells more strongly than IFN-α could [55], a historically controlled clinical trial tested the efficacy of IFN-β-1a in nine EVD patients in Guinea [56]. Within 2 days following qRT-PCR-mediated confirmation of EVD, IFN-β-1a (30 ug/day) was administered SC to patients daily, until patients were tested negative for EBOV, or perished [56].…”
Section: Evd Immunotherapymentioning
confidence: 99%